Unsimulated Sex in Film Simulacra of the Simulation Universe: An Unwatchable Example. - Doğan, Emre (Yedi)
This study was based on film simulacra, which can be regarded as the cinematic manifestation of the claim made by the French sociologist and thinker Jean Baudrillard that reality is destroyed by the perfection of simulation in the post-Second World War era, and that art loses its illusions through the perfection of images. Building on this, the article aimed to provide a Baudrillardian analysis of the concept of unsimulated sex -- that is, sexual intercourse in films that is not imitated -- and its visibility and causality. Two elements highlight the importance and uniqueness of this article. Firstly, the lack of quantitative research on unsimulated sex, a cinematic trend that emerged in the late 1960s, gaining and losing visibility at different times. Secondly, this phenomenon is evaluated in terms of cinematic outputs of Baudrillardian thought. The article's sample was Abdellatif Kechiche's lost film Mektoub, My Love: Intermezzo (2019). Baudrillardian conceptual/theoretical analysis was employed to analyse and express Baudrillardian views based on sociology, art and media in light of this method.